Pharmacological Inhibition of O-GlcNAc Transferase Promotes mTOR-Dependent Autophagy in Rat Cortical Neurons - Rahman, Md Ataur; Cho, Yoonjeong; Hwang, Hongik; Rhim, Hyewhon (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
O-GlcNAc transferase (OGT) is a ubiquitous enzyme that regulates the addition of beta-N-acetylglucosamine (O-GlcNAc) to serine and threonine residues of target proteins. Autophagy is a cellular process of self-digestion, in which cytoplasmic resources, such as aggregate proteins, toxic compounds, damaged organelles, mitochondria, and lipid molecules, are degraded and recycled. Here, we examined how three different OGT inhibitors, alloxan, BXZ2, and OSMI-1, modulate O-GlcNAcylation in rat cortical neurons, and their autophagic effects were determined by immunoblot and immunofluorescence assays. We found that the treatment of cortical neurons with an OGT inhibitor decreased O-GlcNAcylation levels and increased LC3-II expression. Interestingly, the pre-treatment with rapamycin, an mTOR inhibitor, further increased the expression levels of LC3-II induced by OGT inhibition, implicating the involvement of mTOR signaling in O-GlcNAcylation-dependent autophagy. In contrast, OGT inhibitor-mediated autophagy was significantly attenuated by 3-methyladenine (3-MA), a blocker of autophagosome formation. However, when pre-treated with chloroquine (CQ), a lysosomotropic agent and a late-stage autophagy inhibitor, OGT inhibitors significantly increased LC3-II levels along with LC3 puncta formation, indicating the stimulation of autophagic flux. Lastly, we found that OGT inhibitors significantly decreased the levels of the autophagy substrate p62/SQSTM1 while increasing the expression of lysosome-associated membrane protein 1 (LAMP1). Together, our study reveals that the modulation of O-GlcNAcylation by OGT inhibition regulates mTOR-dependent autophagy in rat cortical neurons.